Visible Light Photoelectrocatalytic Degradation of Methylene Blue by Platinum-Treated Carbon Nanotube/Titania Composites - Zhang, Feng-Jun; Chen, Ming-Liang; Oh, Won-Chun (Asian Journal of Chemistry, 2010)
Photoelectrocatalytic degradations of methylene blue in the presence of two types of carbon nanotube/titania and platinum-treated carbon nanotube/titania electrodes in aqueous solutions were studied under visible light. The prepared composite electrodes were characterized by X-ray diffraction, transmission and scanning electron microscopy, energy dispersive X-ray analysis and photoelectrocatalytic activity. It was found that the photoelectrocatalytic degradation of a methylene blue solution could be attributed to the combined effects caused by the photodegradation of titania, the electron assistance of carbon nanotube network, the enhancement of platinum and a function of the applied potential. The composites treated with platnium revealed enhanced photo degradation behaviours of the methylene blue.